A new approach for diagnosing chronic myelomonocytic leukemia using structural parameters of Sysmex XNTM analyzers in routine laboratory practice. (3rd April 2018) - Schillinger, Françoise; Sourdeau, Elise; Boubaya, Marouane; Baseggio, Lucile; Clauser, Sylvain; Cornet, Edouard; Debord, Camille; Defour, Jean-Pierre; Dubois, Frédérique; Eveillard, Marion; Galoisy, Anne-Cécile; Geay, Marie-Odile; et al.
Abstract: According to WHO recommendations, diagnosis of chronic myelomonocytic leukemia (CMML) beforehand requires microscopic examination of peripheral blood to identify dysplasia and/or blasts when monocytes are greater or equal to 1.0 × 10 9 /L and 10% of leucocytes. We analyzed parameters derived from Sysmex TM XN analyzers to improve the management of microscopic examination for monocytosis. We analyzed results of the complete blood count and the positioning and dispersion parameters of polymorphonuclear neutrophils and monocytes in 61 patients presenting with CMML and 635 control patients presenting with a reactive monocytosis. We used logistic regression and multivariate analysis to define a score for smear review. Three parameters were selected: neutrophil/monocyte ratio, structural neutrophil dispersion (Ne-WX) and monocyte absolute value. We established an equation in which the threshold of 0.160 guided microscopic examination in the search for CMML abnormalities with a sensitivity of 0.967 and a specificity of 0.978 in the learning cohort (696 samples) and 0.923 and 0.936 in the validation cohort (1809 samples) respectively. We created a score for microscopic smear examination of patients presenting with a monocytosis greater or equal to 1.0 × 10 9 /L and 10% of leucocytes, improving efficiency in laboratory routine practice.